The leverage externalities of credit default swaps - Li, Jay Yin; Tang, Dragon Yongjun (Journal of Financial Economics, 2016)
This paper provides the first empirical evidence of the externalities of credit default swaps (CDS). We find that a firm's leverage is lower when a larger proportion of its revenue is derived from CDS-referenced customers. This finding is robust to alternative samples and measures, placebo tests, and the selection of customers by suppliers. Moreover, firms affected by customer CDS trading issue equity to lower leverage, and their equity issuance costs are lower. These findings are consistent with the view that CDS trading on customers improves the information environment for suppliers. Therefore, while many firms are not directly linked to CDS trading, CDS trading on their customers has spillover effects on these firms’ financial policies.